Effect of Polyethylene Glycol Chain Length on PEGylation of Dendrimers - Khambete, Hemant (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To check the effect of polyethylene glycol (PEG) chain length on PEGylation of dendrimers. Materials and Methods: In the present work, we have synthesized different PEGylated polyamidoamine dendrimers using six different PEG chains, i.e., PEG - 200, 300, 400, 600, 2000, and 6000. The PEGylated dendrimers were evaluated for color reaction ultraviolet, infrared, and nuclear magnetic resonance studies and compared with standard data. Results and Discussion: The plain dendrimers give violet color due to free NH2 groups. The intensity of violet color of 4.0 G dendrimers decreases on PEGylation, due to attachment of PEG chain on free NH2 groups which is responsible for violet color. The change in Î»max values from 283 to 353 nm was observed, which shows the change in structure of dendrimers. On comparing, it was found that PEG 400 and 600 shows value near their expected values, i.e., 19,150 and 19,780, respectively. Conclusion: From the results of the present study, it can be concluded that PEGylation using PEG 400 and 600 gives a considerable level of attachment of PEG to dendrimers as compared to other PEG chains.